Impact of foreign remittances on school enrolment and educational expenditures in district Peshawar, Pakistan - Sajid Gul (IDEA PUBLISHERS, 2021)
This study aims to identify the effects of foreign remittances on school enrolment and the educational expenditures of children in the Peshawar district. Primary data were acquired by simple random sampling and a questionnaire. Correspondingly, the logit approach and Heckman selection theory were utilized to examine school enrolment and educational expenses. The marginal effects were evaluated to determine the co-efficient. The study's findings indicate that Per Capita Remittances (PCRM) have a highly substantial and beneficial effect on children's school attendance, with a (10.8%) point increase in school enrolment for every 100 rupees rises in Per Capita Remittances (PCRM). Suppose a household's Per Capita Income (PCIM) improves by one hundred rupees, the probability of children enrolling in school increases by (0.17). The results indicate that PCRM and educational costs per kid are significantly and positively correlated. Educational spending per child increases by 12.01 rupees for every 100 rupees rise in family remittances per capita, whereas every 100 rupees increase in per capita income increases educational expenditure per kid by (8.38 PKR). Which leads to an 8.38 % marginal propensity to spend on child education.